Comparative evaluation of pre and post operative functional outcomes determined by Lysholm knee score of patients undergoing arthroscopic anterior cruciate ligament reconstruction - Kapoor, Rajat; Verma, Ashutosh; Saroj, Atul Kumar (International Journal of Research in Orthopaedics, 2022)
Background: The anterior cruciate ligament (ACL) is the primary stabilizer of the knee joint and prevents the knee against anterior translation. After ACL tears, most patients experience recurrent episodes of instability (give way), pain and decreased function. Purpose of our study was to comparative evaluation of functional outcomes of pre and post operative patients after arthroscopic ACL reconstruction by using Lysholm knee score and its complications. Methods: This is a prospective interventional study which were included total 45 patients undergoing arthroscopic ACL reconstruction by using hamstring autograft. Postoperatively patients were followed up at 6, 9 and 12 months for functional assessment by using Lysholm knee score. Results: After ACL reconstruction increment in mean Lysholm knee score during follow up from 69.33 to 96.03 at final followup (p<0.001) which indicate that significant improvement in functional status of patients. Conclusions: Reconstruction of ACL leads the patient to return to a normal activity level and prevent the occurrence of associate meniscal injury and post-traumatic osteoarthritis. A regular followup based and well-organized rehabilitation program provide a key role in functional outcome of knee after ACL reconstruction.